Andic Soil Properties and Tephra Layers Hamper C Turnover in Icelandic Peatlands. Issue 12 (24th November 2021) - Möckel, Susanne Claudia; Erlendsson, Egill; Gísladóttir, Guðrún
Abstract: Due to frequent volcanic activity and erosion of dryland soils, magnified by land use after human settlement (ca. 870 CE), peatlands in Iceland receive regular additions of mineral eolian deposits. Their soils may develop not only histic but also andic characteristics. Yet, mineral eolian deposition as an environmental determinant of peatlands in Iceland is still poorly understood, not least with regard to the peatlands carbon (C) stores. This study advances our understanding of the impact of tephra deposition on Histosols by elucidating interactions between C characteristics and andic soil properties. We compare Histosols from three Icelandic peatlands of different degrees of exposure to eolian deposition by evaluating data sets of their C structure derived by 13 C NMR spectroscopy, andic soil properties based on selective extractions of Al, Fe, and Si, and decomposition proxies C/N, δ 13 C, and δ 15 N. By applying multivariate statistical methods, we are able to present several important patterns. Soil organic matter of Histosols with andic properties is less decomposed than that of Histosols without notable andic properties. Andic soil properties seem to impact their C structure by facilitating the formation of organo‐mineral complexes, which particularly hamper the decomposition of chemically more labile C groups. Tephra layers appear to hamper microbial activity in deeper soil layers by preventing input of fresh organic matter. The interaction of andic and histic soil properties and the protective role of major tephra deposits may enable an unusual potential for long‐term C stabilization in a natural peatland environment. Plain Language Summary: Peatlands belong to the greatest terrestrial carbon stores worldwide. Their organic soils possess exceptional capacities for long‐term carbon storage. Peatlands in Iceland are unusual as they receive comparatively great amounts of windborne mineral material from volcanic eruptions or sparsely vegetated and eroded drylands. These mineral additions of volcanic origin to the otherwise organic substrate of the peatlands shape their soil characteristics and set them apart from similar soils in neighboring countries. On the one hand, they bear characteristics typical for organic soils in Nordic peatlands, on the other hand they possess characteristics of mineral soils of volcanic regions. Little is known about the impact of interactions between these characteristics on the peatlands carbon stores. This study increases our knowledge on carbon storage of peatlands in volcanic regions. We compare soils from three peatlands in northwest Iceland and shed light on interactions between their mineral and organic constituents, with a particular focus on soil organic carbon. We find strong indications that decomposition processes are slower in soils with stronger characteristics of mineral volcanic soils. In undisturbed (anaerobic) peatlands, this seems to impact long‐term carbon storage positively, but in disturbed (aerobic) peatlands, it might pose a threat of accelerated carbon emissions. Key Points: Andic soil properties impact the carbon structure of Histosols of volcanic regions and their carbon storage capacity Andic soil properties and thick tephra deposits appear to enhance long‐term carbon stabilization in undisturbed peatlands Relatively undecomposed Histosols with andic properties may be a greater source of atmospheric carbon upon disturbance than anticipated